Transformasi Pendidikan Agama Islam di Era Kecerdasan Buatan: (Telaah Konseptual terhadap Literasi Digital Religius) - Sumarno Sumarno; Tuti Alawiyah (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
The digital era and the advancement of Artificial Intelligence (AI) have brought fundamental changes in Islamic Religious Education (PAI), demanding pedagogical and curriculum adaptations. This research aims to conceptually examine the transformation of PAI in the AI era, focusing on the crucial role of Religious Digital Literacy (LDR). The method used is a qualitative literature study, analyzing various scientific sources related to PAI, AI in education, and digital literacy. The results show that AI offers significant opportunities for personalization of learning and efficiency, but it also poses ethical challenges, data privacy, and digital divides. LDR is defined as the critical and ethical ability to access, evaluate, and produce digital religious content. This study concludes that LDR is very important to equip students to be able to use AI responsibly, maintain Islamic values, and form "digital wisdom" in the midst of disinformation. The transformation of PAI must be synergistic, integrating AI wisely while strengthening the spiritual and ethical core through a comprehensive LDR.